Continuous transesterification for tubular reactor - Lau, Kun Lu (2015)
Biodiesel production has been use for transportation to replace the petro diesel in Europe country since end of twenty century due to the gasoline and petroleum limitation. Biodiesel are produce from the waste cooking oil through the process of transesterification reaction and assisted by microwave. Transesterification is the most comment process for produce the biodiesel whereby microwave assisted to change the triglyceride(vegetable oil) to biofuel by adding the activated cement clinker (catalyst) and methanol in the condition 60°C with 6 minutes reaction time.The heterogeneous base catalystactivated cement clinker is chosen to use with several advantage such as reusable, environmental friendly and low costs. The microwave assisted in transesterification can reduce the reaction time and also increase the product yield. The catalyst made from cement clinker is activated by potassium hydroxide solution which characterized by several type of test such as Thermogravimetric Analysis, Brunauer-Emmett-Teller test, X-ray Diffraction test and Gas Pyrometer test. The parameter was determiningfor produce the biodiesel by using the activated cement clinker catalyst with the weight ratio(2, 3, 4, 5 and 6% wt.). The result was analysed by using gas chromatography (GCMS) showed that 5% wt. of activated cement clinker use are the optimum amount which having 92.85% conversion and 85.26% yield. For the conventional method by using activated cement clinker and pure calcium oxide obtained 92.63% and 85.37% yield respectively. Based on the yield result, transesterification assisted by microwave method is the best method for the reaction compare with conventional method.